PERAN VISUALISASI LABEL KEMASAN PRODUK MINUMAN USAHA MIKRO KECIL MENENGAH (UMKM) TERHADAP PENGAMBILAN KEPUTUSAN KONSUMEN - Triandi Purnama Ramadhan (Universitas Komputer Indonesia, 2019)
Micro, Small and Medium Enterprises (MSMEs) is a business group that if it is viewed from assets and turnover is under the factory. Yet, MSME products usually have unique criteria: raw materials, production quantities, and target markets. MSMEs are still considered to have weaknesses in packaging design. One of the factors is the limited ability to use tools and technology in creating unique packaging designs and representing brand identity. The solution is to choose the type of ready-made packaging (stock) available on the market, so it is possible that one form of packaging can be used by many brands. So in their marketing, MSMEs should be able to maximize the role of visualization on the packaging label. Fruits Up and Mon ChÃ©rie are examples of MSMEs in Bandung that make fruit-flavored drink products. With the same product category and target market, it is obvious how visualization of the packaging labels they create is reviewed with the 'applied aesthetic' theory chart. Based on the results of the analysis by mixed methods with sequential exploratory strategy, it is found that the visualization role on the packaging label is a major element to differentiate their identity with other products, as well as a means to convey the purpose and uniqueness of each product. The good visual elements on the label must have aesthetic rules, readable, understandable, and right on target. A packaging design can be influenced by the maker (product uniqueness, production capacity, capital, use of technology, tools, and skill) and end user (need, will, lifestyle), then produce impact on the aesthetic, practical, and symbolic aspects of the customer. The conclusion of consumer interpretation is the composition of color and illustration are more effective than other visual elements in order to make it easier for consumers to make purchasing decisions.